Historical Echoes of Teaching English in Primary School in Costa Rica PPEIEP: 1979-1987 - Valenzuela Arce, Nandayure (2013)
Este es uno de un grupo de estudios que presentan una visión integral del quehacer pionero de la Escuela de Literatura y Ciencias del Lenguaje (ELCL) de la Universidad Nacional de Costa Rica en cuanto al desarrollo de la enseñanza comunicativa del inglés a población infantil en nuestro país. Es la reconstrucción histórica del primer proyecto de extensión, en este campo, de la ELCL, denominado Proyecto Piloto de la Enseñanza del Inglés en la Escuela Primaria Pública [1979-1987]. Se informa acerca de las dinámicas del proyecto y sus efectos en la comunidad de docentes de inglés y el estudiantado de primaria en la educación pública. This is one of several studies which present a comprehensive overview of the pioneering efforts of the Escuela de Literatura y Ciencias del Lenguaje (ELCL) at the Universidad Nacional, Costa Rica, in the development of communicative English teaching to elementary school children. Thus, our first effort is to recover the historical memory of the first outreach project developed by the ELCL for that purpose, known as the Pilot Project for the Teaching of English in Primary Public Schools [1979-1987] (Proyecto Piloto de la Enseñanza del Inglés en la Escuela Primaria Pública). Information is provided on the dynamics of the project and its impact on English teachers and students at the public elementary school level.